2017
DOI: 10.1038/s41523-017-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of neoadjuvant talazoparib for operable breast cancer patients with a germline BRCA mutation demonstrates marked activity

Abstract: This study was undertaken to determine the feasibility of enrolling breast cancer patients on a single-agent-targeted therapy trial before neoadjuvant chemotherapy. Specifically, we evaluated talazoparib in patients harboring a deleterious BRCA mutation (BRCA+). Patients with a germline BRCA mutation and ≥1 cm, HER2-negative primary tumors were eligible. Study participants underwent a pretreatment biopsy, 2 months of talazoparib, off-study core biopsy, anthracycline, and taxane-based chemotherapy ± carboplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…Neoadjuvant studies exploit the possibility of PARP inhibitors to potentially spare patients the detrimental toxicities and likely impact on quality of life of chemotherapy, while also obtaining vital information on the underlying tumor biology and responsiveness to PARP-targeted therapy. Recent phase II neoadjuvant trial data for the use of single-agent neoadjuvant talazoparib for patients with BRCA1/2 mutant, HER2 normal (predominantly triple negative) operable breast cancer were very encouraging, with 53% of women on study achieving a pathologic complete response, and over 60% ORR reported during preliminary analysis (74). Toxicities observed were similar to those reported in studies of talazoparib administered in the metastatic setting, including grade 4 thrombocytopenia in 1 of 18 patients, and dose reductions were required in 9 of 18 patients.…”
Section: Extending the Clinical Benefits Of Parp Inhibitorsmentioning
confidence: 99%
“…Neoadjuvant studies exploit the possibility of PARP inhibitors to potentially spare patients the detrimental toxicities and likely impact on quality of life of chemotherapy, while also obtaining vital information on the underlying tumor biology and responsiveness to PARP-targeted therapy. Recent phase II neoadjuvant trial data for the use of single-agent neoadjuvant talazoparib for patients with BRCA1/2 mutant, HER2 normal (predominantly triple negative) operable breast cancer were very encouraging, with 53% of women on study achieving a pathologic complete response, and over 60% ORR reported during preliminary analysis (74). Toxicities observed were similar to those reported in studies of talazoparib administered in the metastatic setting, including grade 4 thrombocytopenia in 1 of 18 patients, and dose reductions were required in 9 of 18 patients.…”
Section: Extending the Clinical Benefits Of Parp Inhibitorsmentioning
confidence: 99%
“…27 The use of PARP inhibition is also being explored in patients with early-stage breast cancer and germline BRCA mutations, including in the neoadjuvant and adjuvant settings. [28][29][30][31] The randomized OlympiA phase III study will examine adjuvant use of olaparib in patients with high-risk HER2-negative breast cancer with gBRCA mutations and should reveal whether PARP inhibition can improve outcomes in breast cancer if given in an earlier setting. 31 NOTE.…”
Section: Dna Damagementioning
confidence: 99%
“…A pilot study by the same group investigated single-agent talazoparib for 2 months in a similar patient cohort, followed by standard chemotherapy, and results showed that all 13 patients enrolled had a decrease in tumor volume, with an average reduction of 78% (range, 30%-98%). 30…”
Section: Parpi In Early-stage Breast Cancermentioning
confidence: 99%